2003
DOI: 10.1140/epjb/e2003-00034-6
|View full text |Cite
|
Sign up to set email alerts
|

The high-pressure ?/? phase transition in lead sulphide (PbS)

Abstract: Abstract. The high-pressure behaviour of PbS was investigated by angular dispersive X-ray powder diffraction up to pressures of 6.8 GPa. Experiments were accompanied by first principles calculations at the density functional theory level. By combining both methods reliable data for the elastic properties of rock-salt type α-and high-pressure β-PbS could be obtained. β-PbS could be determined to crystallise in the CrB-type (B33), with space group Cmcm. The reversible ferro-elastic α/β transition is of first ord… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
53
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 30 publications
14
53
0
Order By: Relevance
“…Our calculations are in good agreement with experimental results [32][33][34][35], and we predict new modifications [36]. Furthermore, a global optimization in the ZnO system was performed with an empirical potential for a number of different pressures, followed by refinement on ab initio level.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Our calculations are in good agreement with experimental results [32][33][34][35], and we predict new modifications [36]. Furthermore, a global optimization in the ZnO system was performed with an empirical potential for a number of different pressures, followed by refinement on ab initio level.…”
Section: Resultssupporting
confidence: 82%
“…PbS undergoes a pressure-induced phase transition from the NaCl (B1) type to an intermediate orthorhombic phase (suggested to belong to the B16 or B33 structure types at 2.2 GPa [32][33][34]. A further pressure-induced phase transition from the orthorhombic phase to the CsCl type (B2) phase takes place at 21.5 GPa [32].…”
Section: Lead Sulfide (Pbs)mentioning
confidence: 99%
“…Using resistance measurements, Samara et al found that PbS has a phase transition at 2.3-2.5 GPa. 4 X-ray diffraction (XRD) studies have shown that the B1 phase transforms into an intermediate phase at 2-3 GPa, [5][6][7][8][9][10][11][12] and into a CsCl-type structure (B2) at higher than 21.5 GPa. 6,7 However, the detailed structure of the intermediate phase is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed to be Pnma 5 or Cmcm. 6,7,[9][10][11][12] Using angle dispersive XRD studies, Maclean et al found that the intermediate phase could be considered to be a GeS-like structure and can be indexed as a monoclinic structure when including weak reflections. 8 Similarly, various results have been obtained when using different theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The compound undergoes a B1 to B2 transition; the transition proceeds through an intermediate amorphous phase found between [17][18][19][20][21][22][23][24][25][26] GPa that is quenchable down to ambient conditions. The pressure induced structural transition observed in this compound is the first of its type reported in this ternary cubic family, and it is new for the B1-B2 transition pathway reported to date.…”
mentioning
confidence: 99%